2021
DOI: 10.1155/2021/7119779
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Normal Range for Thromboelastography in Healthy Middle-Aged and Elderly People of Weihai in China

Abstract: TEG can monitor the dynamic changes of blood clot formation and lysis by activating the coagulation system of a small sample of whole blood in vitro. The parameters can reflect the level of coagulation factors, the function of fibrinogen and platelet, and the presence or absence of hyperfibrinolysis. At present, the normal reference range of the parameters of TEG is mainly based on the reference values established by the Western population. Due to the differences in the distribution of ethnic groups, many coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 16 publications
(21 reference statements)
1
38
0
Order By: Relevance
“…The sites vulnerable to such injuries include IVC, abdominal aorta, and other organs. It has been reported that the incidence of complications associated with abdominal Trocar insertion is about 0.8 for every 1000 insertions performed [ 2 ]. Such conditions are more likely to happen at the departments of general surgery (the incidence being 0.5–5%) [ 3 ], hepatobiliary surgery, gynecology, chest surgery, and cardiology, where mature minimally invasive procedures, including radiofrequency ablation for atrial fibrillation, are performed [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sites vulnerable to such injuries include IVC, abdominal aorta, and other organs. It has been reported that the incidence of complications associated with abdominal Trocar insertion is about 0.8 for every 1000 insertions performed [ 2 ]. Such conditions are more likely to happen at the departments of general surgery (the incidence being 0.5–5%) [ 3 ], hepatobiliary surgery, gynecology, chest surgery, and cardiology, where mature minimally invasive procedures, including radiofrequency ablation for atrial fibrillation, are performed [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, according to the International Diabetes Federation (IDF) statistics: at present, 382 million people worldwide are threatened by DM. It is estimated that in the next 25 years, the number of people suffering from DM will reach or exceed 592 million [ 2 ]. Today, about 80% of DM patients in the world live in middle- or low-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Individual self-identity of college students has an important influence on stress coping level, anxiety, and depression, which is of great significance to the harmonious development of individual psychology [ 1 ]. Studies have shown that a high sense of self-identity is associated with mental health, while a low sense of self-identity is associated with depression.…”
Section: Introductionmentioning
confidence: 99%